FINANCIAL AND ECONOMIC MECHANISMS OF PUBLIC CONTROL IN FISCAL POLICY TO REDUCE SHADOW ECONOMIC ACTIVITY (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
In recent years, the Republic of Uzbekistan has been carrying out consistent reforms to reduce shadow economic activity. The shadow economy is especially widespread in retail trade, public catering, and the service sector, and the main form of tax evasion is trading without cash registers or electronic payment instruments.